EARLY PREGNANCY DIAGNOSIS IN WATER BUFFALOES USING TRANSRECTAL ULTRASONOGRAPHY - AWASTHl, M K; KHARE, ABHISHEK; KAVANI, F S; SIDDIQUEE, G M; DHAMI, A J (The Indian Journal of Animal Reproduction, 2011)
The objective of present study was to evaluate the accuracy of simplified technique of pregnancy diagnosisat an early stage using transrectal ultrasonography (TRUS) in milch water buffaloes. The diagnosis of pregnancywas primarily based on visualization of embryonic vesicle and observation of embryo was compromised withdetection of embryonic vesicle for determination of pregnancy. The uterine horn ipsilateral to ovary bearing corpusluteum (CL) was scanned through serial ultrasound scanning on Days 23, 25, 28 and 30 post-service in freshlybred Mehsana buffaloes (n=40) for pregnancy diagnosis. Sensitivity and negative predictive value of early pregnancydiagnosis was 100% on each day of TRUS, but the specificity was lower on Days 23 and 25 than Days 28 and 30.Specificity (93.3% ), positive predictive value (96.1 % ) and accuracy (97 .5%) were maximum and similar on Days28 and 30 post-service. The embryo was first observed on 26.33 ± 0.52 (mean± SE) days post-service, while theheartbeats were first detected on 29.25 ± 0.36 days post-service; however, embryo could be visualized in 17 out of25 pregnant animals. The mean length and diameter of embryonic vesicle were recorded as 15.5 ± 0.94 and 6.5 ±0.55 mm on Day 23, which increased to 24.1 ± 1.07 and 9.6 ± 0.77 mm, respectively, on Day 30 post-service. It isconcluded that detection of early pregnancy in buffaloes may be accomplished on and after Day 28 post-servicethrough TRUS with positive predictive value and diagnostic accuracy over 96% and observation of embryo may becompromised with detection of embryonic vesicle for confirmation of pregnancy during early stage.
Keywords: Water buffaloes; Ultrasonography; Early pregnancy diagnosis